2009
DOI: 10.1021/jf900698x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inulin Supplementation Does Not Promote Colonic Iron Absorption in a Porcine Model

Abstract: Prebiotics may enhance iron bioavailability by increasing iron absorption in the colon. Anemic pigs fitted with cecal cannulas were fed a low-iron diet with or without 4% inulin. Over 7 days, pigs were administered 1 mg of (54)Fe in the morning feed followed by cannula infusion of 0.5 mg of (58)Fe to measure total and colonic iron absorption, respectively. Whole blood was drawn prior to the initial dosing and 14 days thereafter for hemoglobin concentration and stable isotope ratio analyses. The prebiotic role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
0
23
0
1
Order By: Relevance
“…Tako et al (2008) also observed an up-regulation of genes encoding Fe transporters in the colon of anaemic piglets fed inulin for 6 weeks. On the other hand, Patterson et al (2010) failed to demonstrate a positive effect after inulin feeding on Fe absorption in the colon. These discrepancies may be related to the different experimental protocols (Scholz-Ahrens & Schrezenmeir, 2007) utilised, because these effects can be influenced by the animal model evaluated (rats, pigs), as different models respond differently to the consumption of fermentable carbohydrates (Scholz-Ahrens & Schrezenmeir, 2007).…”
Section: Variablementioning
confidence: 82%
See 1 more Smart Citation
“…Tako et al (2008) also observed an up-regulation of genes encoding Fe transporters in the colon of anaemic piglets fed inulin for 6 weeks. On the other hand, Patterson et al (2010) failed to demonstrate a positive effect after inulin feeding on Fe absorption in the colon. These discrepancies may be related to the different experimental protocols (Scholz-Ahrens & Schrezenmeir, 2007) utilised, because these effects can be influenced by the animal model evaluated (rats, pigs), as different models respond differently to the consumption of fermentable carbohydrates (Scholz-Ahrens & Schrezenmeir, 2007).…”
Section: Variablementioning
confidence: 82%
“…Previous studies have used different experimental models to assess the influence of bacterial fermentation of non-digestible carbohydrates on Fe absorption and bioavailability (Hara, Onoshima, & Nakagawa, 2010;Patterson et al, 2010;Tako et al, 2008;Yasuda et al, 2006). Yasuda et al (2006) observed increased HRE in piglets fed diets containing 4% purified ITF (inulin), which correlated with soluble Fe concentrations in the large intestine contents.…”
Section: Variablementioning
confidence: 99%
“…In previous years and for in vivo studies using animals, rodents have been the predominant model for Fe bioavailability but appear to have fallen out of favor in recent years due to relatively high efficiency of absorption from foods that have very low availability in humans [73,74]. Piglets have been used as a model but have both strong similarities and differences to human gastrointestinal physiology [74].…”
Section: Introductionmentioning
confidence: 99%
“…Piglets have been used as a model but have both strong similarities and differences to human gastrointestinal physiology [74]. The most readily apparent macroscopic difference between human and porcine is intestine length.…”
Section: Introductionmentioning
confidence: 99%
“…While a stable isotope study by Patterson et al [10] with anemic piglets surgically fitted with cecal cannulas showed that FOS had no enhancing effect on iron absorption in the colon, Tako et al [11] observed that FOS supplementation triggered an upregulation of genes encoding iron transporters in the enterocytes from the duodenum and colon of anemic piglets. In another study using the porcine model, Samolińska and Grela [12] reported increases in iron, zinc and copper concentrations in blood plasma during the fattening period with FOS supplementation.…”
Section: Introductionmentioning
confidence: 99%